Optimal Allocation of Distributed Generations Considering Demand Response and Multi-agent Benefits - Hu, Jing; Ding, Tong; Chen, Hongkun; Xiang, Chaoyang (2020 IEEE 4th Conference on Energy Internet and Energy System Integration (EI2), 2020)
Traditional power planning takes the distribution network as the only agent without fully considering the environmental cost and demand response. However, environmental cost, demand response and multi-agent benefits have begun to receive attention in power planning with the increase of new energy penetration, the development of active distribution networks and the reform of the power market. Firstly, considering three different agents including the power supply side, the distribution network and the users, the optimal allocation models are established with the goal of the maximum net income, respectively. Secondly, according to the relationship of the multi-agent interests, the objective function that considers the net income of all three parties is constructed, and the original model is transformed into a second-order cone programming problem by using the second-order cone relaxation technology. Finally, taking the IEEE33 bus distribution network as a simulation case, the simulation is carried out based on the actual data of loads, wind power outputs and photovoltaic outputs in a regional power grid. The result verifies that the optimal allocation model can effectively improve the overall economic benefits of each subject, and considering environmental costs and demand response in power planning can make the obtained schemes pay attention to both economy and environmental protection, which is in line with the future development trend of power grid.